Via Aurelia Antica/Rom, Italien: Columbarium des C. Scribonius Menophilus - Fröhlich, Thomas (e-Forschungsberichte des DAI, 2023)
A new documentation done with a 3D-laser-scanner was used to do research on the building technique and the equipment of the early-Augustan colombarium with about 500 burials. The standardized niches were individualized by the single owners in different ways and in some cases also the original paintings were replaced by new iconographies or stucco-reliefs. The painted garland in the lower part of the walls could be supplemented by a real garland, which is proved by the evidence of nails found at the top of nearly every niche.